Effect of Levamisole hydrochloride and Corticosteroid on lymphoid organs of laboratory animals - Ramesh, Geetha; Sivakumar, M. (Indian Journal of Veterinary Anatomy, 2018)
To study the effect of Levamisole hydrochloride and the corticosteroid on the lymphoid organs, four, 8 week-old animals of all the three species were used. In the thymus, in levamisole hydrochloride injected animals, no appreciable structural changes could be observed as against their respective controls. There was more number of lymphocytes infiltrated in the red pulp of the spleen in the present study. Among the corticosteroid treatment animals, the involutory changes in the thymus were marked only in the mice and rats. The nodular population was found decreased in the corticosteroid treated animals in the white pulp in all the species studied. The mesenteric lymph node had no marked changes between the three species excepting the formation of germinal centre.